Sucrose metabolism in coffee submitted to different shade levels - Baliza, Danielle Pereira; Santos, Meline Oliveira; Alves, José Donizeti; Guimarães, Rubens José; Cunha, Rodrigo Luz da (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the activity of the enzymes involved in the sucrose metabolism and the carbohydrate levels on the endosperm of the coffee fruit under different shade levels. Four replicater were used, totaling 20 plots, which consisted of eight useful plants. Treatments were arranged in a randomized block design in a 5 x 3 factorial outline, being five shade levels (full sun, 35, 50, 65 and 90% shade) and three fruit development stages (green, green-yellow and cherry). The variables analyzed were the activities of the enzymes sucrose-phosphate synthase (SPS), sucrose synthase (SuSy) and acid invertase and total soluble sugars, sucrose and glucose content. The shading higher than 50% increased the activity of acid invertase and SuSy in green-yellow and cherry stages. Regarding the SPS, shading did not alter its activity, the highest values were found in the green-yellow and cherry stages. The shading levels up to 65% have the highest soluble sugar levels and sucrose in the late stages of maturation while for the 90% shading, the highest values were found in the early stages of fruit development. The glucose content was higher in the green maturation stage, up to the level of 50% shading, from which there is a decrease in glucose values with increased shading. Thus, it appears that shading higher than 50%, probably modifies the fruit development by affecting the metabolism of sucrose in the endosperm, prolonging the maturation period.